Reconciling Mountain Biodiversity Conservation in a Changing Climate: A Hindu Kush-Himalayan Perspective - Chettri, Nakul (Conservation Science, 2015)
Mountains occupy 24% of the global land surface area and are home to 12% of the world’s population. They have ecological, aesthetic, and socioeconomic significance, not only for those living in mountain areas, but also for people living beyond. The Hindu Kush-Himalayan region (HKH) expanding to over four million square kilometres is endowed with rich biodiversity, culture, and sources of varied goods and services that serve more than 200 million people living in the region and 1.3 billion people living in the river basins receive services from them. The countries sharing the HKH have set aside 39% of the biodiversity rich area for different systems of protection. However, in the recent years, the HKH is facing numerous drivers of environmental change including climate change. Various studies suggest that warming in the HKH has been much higher than the global average over the last 100 years and the HKH is already facing climate change threats at ecoregions, ecosystems and species levels. While climate change is a global problem requiring a global solution, the HKH countries have initiated various reconciling initiatives to link conservation with climate change for enhancing ecological and socio-economic resilience. However, there is serious paucity of expertise, capacity and data on climate change as well as biodiversity in the HKH bringing challenges in enhancing the resilience. Considering the significance of the HKH on local, regional, and global levels, it is imperative to close the gaps to meet the challenges arising from the consequences of climate change. International Centre for Integrated Mountain Development (ICIMOD), with its partners, has conceptualised a number of innovative conservation approaches with an objective to reconcile biodiversity conservation goals with climate change challenges. These conservation approaches have a huge potential for mutual benefits from the common good practices, resources and expertise and there is a need for more formal cooperative agreements between the various institutions and communities of the countries at the regional level for addressing regional issues of conservation in the changing climate. Conservation Science Vol.2(1) 2014: 17-27